A condition called love. 3 - Morino, Megumi (Kodansha USA Publishing, 2023)
"Wise men say only fools rush in... After extending the length of their "trial relationship," Hotaru has done what she thought was impossible: developed romantic feelings for Hananoi-kun! But just as she starts to face this reality, she is reunited with a boy from her past..."--